2003
DOI: 10.1191/0265532203lt258oa
|View full text |Cite
|
Sign up to set email alerts
|

Comparability of a paper-based language test and a computer-based language test

Abstract: With the advent of the digital revolution, language testers have endeavored to utilize state-of-the-art computer technology to satisfy the ever-growing need for a tool to measure English communication skills with maximal accuracy and efficiency. Thanks to the concerted efforts made by experts in such fields as computational linguistics, computer engineering, computer-assisted language learning, and psychometrics, language testers have recently succeeded in developing computer/web-based language tests. Among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(76 citation statements)
references
References 23 publications
4
63
1
4
Order By: Relevance
“…Furthermore, Boo et al (2012) found that although test takers preferred computer counterpart of the conventional test, the scores received from CBT and PPT were comparable in terms of internal consistency, criterion and construct validities, means and standard deviations. Choi, Kim, and Boo (2003) reported that the results of paper and computer versions of the standardized English language test administered to post-secondary level language learners were comparable. They proved that two versions of listening, reading comprehension, grammar and vocabulary subtests measured the same constructs based on confirmatory factor analysis results.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Boo et al (2012) found that although test takers preferred computer counterpart of the conventional test, the scores received from CBT and PPT were comparable in terms of internal consistency, criterion and construct validities, means and standard deviations. Choi, Kim, and Boo (2003) reported that the results of paper and computer versions of the standardized English language test administered to post-secondary level language learners were comparable. They proved that two versions of listening, reading comprehension, grammar and vocabulary subtests measured the same constructs based on confirmatory factor analysis results.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous other studies in which the technique of correlation has been used correctly. The most recent studies in this category are (Choi et al 2003), (Trites and McGroatry 2005) and (Roever 2006), to name a few. (Roever 2006), for instance, compared web-based tests of implicatures, routines and speech-acts and found that the tests were related, without claiming that they could be substituted.…”
Section: Methodsmentioning
confidence: 99%
“…The related notion of correspondent results both is PBT and CBT was also reinforced by many studies in certain specific subject areas, and the clear discrimination of results was established in achievement tests such as science, language and mathematics, and also the same was very perceptibly ascertained by a chain of psychological tests such as personality and neuropsychological assessment (e.g., Friedrich & Bjornsson, 2008;Choi, Kim, & Boo, 2003;DeAngelis, 2000). In their findings about the review of educational and psychological measurement approaches, Bunderson, Inouye & Olsen (1989) have established that 48% of previous studies revealed negligible difference between the two testing modes (PBT & CBT) in the area of test performance, whereas 13% of studies have reported that CBT test performance is better than PBT and 39% of findings have proved PBT better than CBT.…”
Section: Introductionmentioning
confidence: 90%